2022
DOI: 10.3389/fonc.2022.659812
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis in Male Breast Cancer With Bone Metastasis Based on the SEER Database

Abstract: PurposeBreast cancer (BC) has been extensively and deeply studied as the number one malignant tumor in women, but its status in male patients, especially in male metastatic patients, is rarely reported. Thus, this study aimed to explore the prognosis and risk factors of male BC with bone metastasis.Patients and MethodsWe searched the Surveillance, Epidemiology, and End Results (SEER) database to identify all patients diagnosed with male BC with bone metastasis from 2010 to 2016. Risk factors of overall surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…However, in our multivariate analysis, chemotherapy and radiotherapy did not significantly enhance the prognosis in MBCBM patients (P>0.05). Thankfully, our conclusion was not exceptional and was supported by Zhou et al (14). Of course, this could be owing to the absence of critical information in the SEER database, such as therapeutic drugs and doses, patient responsiveness, and compliance, preventing indepth analysis.…”
Section: Malignant Tumor Cells Interfere With Bone Microenvironment H...supporting
confidence: 61%
See 3 more Smart Citations
“…However, in our multivariate analysis, chemotherapy and radiotherapy did not significantly enhance the prognosis in MBCBM patients (P>0.05). Thankfully, our conclusion was not exceptional and was supported by Zhou et al (14). Of course, this could be owing to the absence of critical information in the SEER database, such as therapeutic drugs and doses, patient responsiveness, and compliance, preventing indepth analysis.…”
Section: Malignant Tumor Cells Interfere With Bone Microenvironment H...supporting
confidence: 61%
“…Therefore, they have not been incorporated into our nomograms. The article from Zhou et al also supported this result (14). Metastasis in one organ might accelerate the spread of cancer cells to other organs, and BM could considerably enhance the risk of other metastases and vice versa (4,18).…”
Section: Malignant Tumor Cells Interfere With Bone Microenvironment H...mentioning
confidence: 79%
See 2 more Smart Citations
“…However, there is minimal evidence to support the hypothesis that men with HER2-positive breast cancer bene t from surgery. However, studies have shown that surgery brings longer survival for HER2-positive breast cancer patients [23]as well as men with breast cancer [24]. It is well-known that chemotherapy is an important treatment for malignant tumors.…”
Section: Discussionmentioning
confidence: 99%